A two-photon ESIPT based fluorescence probe for specific detection of hypochlorite - Chen, Liyan; Park, Sang Jun; Wu, Di; Kim, Hwan Myung; Yoon, Juyoung (Dyes and Pigments, 2018)
Hypochlorous acid (HOCl) is one important member of reactive oxygen species (ROS) familyresponsible for various human diseases. Although many contributions have been made to develop fluorescent probes for sensing HOCl, many of them suffer small Stokes shifts, sophisticated synthetic procedure, and slow reaction rate. In the current study, we designed and synthesized an ESIPT based fluorescence probe with diaminomeleonitrile (DMN) as reactive site. The probe can detect HOCl with high selectivity and sensitivity. It also has large Stokes shift and rapid reaction rate. Moreover, it can be utilized to monitor exogenous and endogenous HOCl in living cells and tissues via two-photon microscopy.
Keywords: ESIPT; Hypochlorite; Living cell; Tissue imaging; Two photon; ESIPT; Hypochlorite; Living cells; Tissue imaging; Two-photon